A highly stable CoMo2S4/Ni3S2 heterojunction electrocatalyst for efficient hydrogen evolution. Issue 6 (23rd December 2020) - Wang, Minmin; Zhang, Mengke; Song, Wenwu; Zhong, Weiting; Wang, Xunyue; Wang, Jin; Sun, Tongming; Tang, Yanfeng
Abstract : A CoMo2 S4 /Ni3 S2 heterojunction is prepared with an overpotential of only 51 mV to drive a current density of 10 mA cm −2 in 1 M KOH solution and ∼100% of the potential remains in the ∼50 h chronopotentiometric curve at 10 mA cm −2 . Abstract : A CoMo2 S4 /Ni3 S2 heterojunction is prepared with a high charge carrier mobility and many active sites. This CoMo2 S4 /Ni3 S2 electrode requires an overpotential of only 51 mV to drive a current density of 10 mA cm −2 in 1 M KOH solution. Impressively, the as-prepared electrode exhibits a high stability, with ∼100% of the current density remaining in the ∼50 h amperometric curve both at 10 mA cm −2 and 240 mA cm −2 .